Accompanying as a professional posture at the crossroads between research interests and training needs - Montalbetti, Katia (Formazione & insegnamento, 2017)
Criticism about the low impact of research on educational processes has led to questioning the traditional research devices centered on the researcher’s external position. The myth of objectivity has been progressively replaced by the recognition of interpersonality and a reduced interpretation of validity is accompanied by a wider scope to consider, in addition to the technical dimension, the ecological one. Training, for those working in professional contexts, has also shown little impact on the contexts when it adopts traditional forms that fail to capture real needs of both professionals and organizations. These evidences have led to a general rethinking of the training design, based on the recognition of the principles already laid out in the field of adult education. The internal review in research and training practices has led to reflection and problematization of the rigid distinction between places and logic of research and training. In this perspective, the paper focuses on accompaniment as a professional posture that qualifies and specifies researcher in educational context.